Analisis Teknikal dan Rasio Keuangan Untuk Investasi Pada Industri Pembangkit Listrik Energi Terbarukan Untuk Ekonomi Berkelanjutan - Bahri, Nugraha Miftahul; Hakim, Abdul (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The purpose of this research is to find a company with a good portfolio and history so that investors can use it to evaluate renewable energy companies listed on the IDX. The research method used is descriptive-quantitative. The results of the study show that, based on the current ratio, TGRA issuers have a higher current ratio of 106%. Similar to return on equity, TGRA issuers for 2021 have a higher dividend policy than BRBN. When viewed from the price-to-book value ratio, the two issuers have a lower share price compared to their book value. From the standpoint of BNBR earnings per share, it can be stated that it is better with the impact that BNBR issuers' income is higher than that of TGRA issuers for 2021. Meanwhile, the price-earnings ratio for TGRA is higher than BNBR for 2021, indicating that TGRA is more intense. higher return on investment compared to BNBR for investors who want a faster return on investment and faster profits. so that investors' decisions to invest their shares in TGRA tend to be more desirable and have better prospects in terms of price-to-earnings ratio compared to BNBR issuers.